Melatonin Promotes the Chilling Tolerance of Cucumber Seedlings by Regulating Antioxidant System and Relieving Photoinhibition - Zhang, Xiaowei; Feng, Yiqing; Jing, Tongtong; Liu, Xutao; Ai, Xizhen; Bi, Huangai (Frontiers in Plant Science, 2021)
Chilling is a major stress which adversely decreases photosynthesis and leads to oxidative stress in thermophilic plants. The role of melatonin (MT) in stress response of plants, has so far been investigated, while the mechanisms by which MT regulate photosynthesis in chilling-sensitive cucumber under chilling stress remain unclear. In this paper, we reported MT positively regulated chilling tolerance of cucumber. Moreover, MT showed a concentration-dependent manner and 1.0 μmol·L-1 was the optimum concentration, of which the chilling injury index, EL and MDA were the lowest, while growth was the highest among all the treatments. Further studies indicated that MT triggered the activity and expression of the antioxidant enzymes, which in turn decreased ROS accumulation caused by chilling stress. Meanwhile, MT maintained a high photosynthetic carbon assimilation capacity, increased the activity of PSI reaction center, PSII reaction center and electron transfer efficiency. More importantly, the proteome analysis and western-blot data revealed that PSI-associated proteins (PsaD, PsaE, PsaF, PsaH and PsaN), PSII-associated protein D1 as well as Rubisco large subunit and RCA were significantly up-regulated in MT-treated seedlings, compared to H2O-treated seedlings under chilling stress. These results suggest that MT enhances chilling tolerance of cucumber via activating the antioxidant system as well as protein level of key PSI-, PSII-related and carbon assimilation enzymes to decrease ROS accumulation, and finally alleviates the damage to photosynthetic apparatus under chilling stress.